2014
DOI: 10.1590/1806-9282.60.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between body mass index and overactive bladder symptoms in pre-menopausal women

Abstract: Correlation between body mass index and overaCtive bladder symptoms in pre-menopausal women rev assoC med bras 2014; 60 (2) Conflict of interest: noneObjective: The aim of the study was to establish a correlation between Overactive Bladder (OAB) symptoms and Body Mass Index (BMI) in women aged 20-45. Methods: We interviewed 1.050 women aged 20-45 in the area of Campinas, Brazil, to investigate the prevalence of overactive bladder symptoms. In this study, we used the ICIQ-OAB questionnaire (ICS standard), in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
0
11
1
4
Order By: Relevance
“…This will explain the decrease of SUI and increase of MUI with enhancing BMI. However, this is uncertain since inconsistent results exist regarding the association between the different subtypes of UI and BMI . This diversity is probably due to pure differentiation between the subtypes of UI, and systematic bias, due to self‐reporteding of weight and height.…”
Section: Discussionmentioning
confidence: 99%
“…This will explain the decrease of SUI and increase of MUI with enhancing BMI. However, this is uncertain since inconsistent results exist regarding the association between the different subtypes of UI and BMI . This diversity is probably due to pure differentiation between the subtypes of UI, and systematic bias, due to self‐reporteding of weight and height.…”
Section: Discussionmentioning
confidence: 99%
“…Women with BMI ≥30 presented more nocturia and more urgency cases than women with normal BMI. A significant difference was also found regarding urge-incontinence; women with BMI 25–29.9 presented a higher score than women in the 18.5–24.9 group (p=0.0017) [ 33 ].…”
Section: Obesity As a Risk Factor Of Urinary Incontinence And Pelvic mentioning
confidence: 99%
“…Palma et al showed a correlation between overactive bladder symptoms and BMI among 1050 middle-aged women. They reported a statistically significant difference in terms of nocturia, urgency, and urge incontinence in women with a BMI ≥ 30 compared with women with a BMI < 25 [ 19 ]. Similarly, Chang et al stated that children with a higher BMI had higher urgency symptoms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%